MENGUASAI PENGETAHUAN KONSEPTUAL DAN PRAKTIS TENTANG TEORI DAN KONSEP BIAYA - Firabiawwalia, Salsabila Shafha; Fahri, Agung; Romlah, Romlah; Noviariati, Heni (STKIP Pesisir Selatan, 2025)
A deep understanding of cost theory and concepts is crucial in supporting managerial decision-making, strategic planning, and performance evaluation in business and education. This article aims to explore and analyze the mastery of conceptual and practical knowledge of students and practitioners of cost theory, types of costs, and their application in operational activities. This research uses a descriptive qualitative approach with literature study techniques and field observations in academic environments and small-medium scale businesses. The results show that there is a gap between the theoretical understanding obtained through formal learning and practical application in the field, especially in the classification of fixed, variable, direct, indirect, and relevant costs. This article suggests the need for integration between real case-based learning and the utilization of digital technology in the learning process of cost theory in order to have a more applicable and contextual understanding. These findings can be the basis for curriculum development that is more responsive to labor market needs.